Riesgo cardiovascular en trabajadores de la Cooperativa de Transportes Loja Internacional - Santín Jaramillo, Arianna Elizabeth (2021)
Cardiovascular diseases are the leading cause of death in the world. The profession of driver is considered high risk due to the long working hours in sedentary lifestyle that influence the development of unhealthy lifestyle habits, therefore, the objectives of this study were to classify the level of cardiovascular risk, identify risk factors and analyze the predictive tables of cardiovascular risk in the drivers of the Cooperativa de Transportes Loja Internacional who worked during the months of December 2019 - May 2020. It was a mixed-approach, descriptive and cross-sectional cohort study, prospective; the population consisted of 85 participants who met criteria in whom the data collection sheet, IPAQ physical activity questionnaire and cardiovascular risk prediction charts Globorisk Ecuador and Gaziano were applied. The results obtained were that the risk of suffering a cardiovascular event in 10 years is low (<10%) with 90.00% (n=64) in the Globorisk chart and 58.82% (n=50) in the Gaziano chart, followed by moderate risk (10 to 20%) with results of 10.00% (n=6) and 35.29% (n=30) respectively; finally, the high risk was only identified in the Gaziano chart with 4.67% (n=5). The risk factors that predispose to developing cardiovascular disease identified were BMI > 25, low level of physical activity, abdominal perimeter > 102 cm, SBP > 140 and/ o DBP > 90 mmHg, cigarette and alcohol consumption. Most of these risk factors are preventable and can be modified through healthy lifestyle habits reducing the risk of a cardiovascular event; In addition, the importance of the use of risk predictor tables for screening, monitoring and health education for the patient is highlighted. Keywords: risk factors, cardiovascular diseases, primary prevention, risk assessment